Targeting hypoxic cells through the DNA damage response - Olcina, Monica (2010)
Exposure to hypoxia-induced replication arrest initiates a DNA damage response which includes both ATR and ATM-mediated signalling. DNA fiber analysis was used to show that these conditions lead to a replication arrest during both the initiation and elongation phases and that this correlated with decreased levels of nucleotides. The DNA damage response induced by hypoxia is distinct from the classical pathways induced by damaging agents primarily due to the lack of detectable DNA damage but also due to the coincident repression of DNA repair in hypoxic conditions. The principle aims of the hypoxia-induced DNA damage response appear to be the induction of p53-dependent apoptosis or the preservation of replication fork integrity. The latter is of particular importance should reoxygenation occur. Tumor reoxygenation occurs as a result of spontaneous changes in blood flow and also therapy. Cells experiencing hypoxia/reoxygenation are therefore sensitive to loss or inhibition of components of the DNA damage response including; Chk1, ATM, ATR and PARP. In addition, restoration of hypoxia-induced p53-mediated signalling may well be effective in the targeting of hypoxic cells. The DNA damage response is also induced in endothelial cells at moderate levels of hypoxia which do not induce replication arrest. In this situation phosphorylation of H2AX has been shown to be required for proliferation and angiogenesis and is therefore an attractive potential therapeutic target.